PENGARUH PENILAIAN KINERJA DAN PEMBERDAYAAN KARYAWAN TERHADAP KOMITMEN ORGANISASI DAN KEPUASAN KERJA SEBAGAI VARIABLE INTERVENING (Studi Empiris Pada PT. Permodalan Siak ) - Abdullah Pendi; Rosnelly Rosnelly; Mida Aprilina Tarigan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The purpose of this study was to determine the effect of performance appraisal,employee empowerment on organizational commitment through employee job satisfactionat PT. Siak Capital. The data used are primary and secondary data. Primary data wasobtained by interviewing a sample of 62 employees. Hypothesis Testing Using PathAnalysis Model (Path Analysis). The results of this study indicate that there is a positiveeffect of performance appraisal on organizational commitment, there is a positiveinfluence of employee empowerment on organizational commitment, there is a positiveinfluence of performance appraisal on job satisfaction, there is a positive influence of jobsatisfaction on organizational commitment, there is a positive influence of empowermentemployees on job satisfaction, greater direct effect of performance appraisal onorganizational commitment through job satisfaction than the direct effect, greater directinfluence of employee empowerment on organizational commitment through jobsatisfaction than direct influence.Keywords:Performance Assessment, Employee Empowerment, OrganizationalCommitment, Job Satisfaction.